2002
DOI: 10.1017/s1041610202008281
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric MRI Measurements Can Differentiate Alzheimer's Disease, Mild Cognitive Impairment, and Normal Aging

Abstract: Background: Volumetric magnetic resonance imaging (MRI) has been extensively studied in the last decade as a method to help with the clinical diagnosis of Alzheimer's disease (AD). In recent years, researchers have also started investigating if that technique would be useful to identify individuals with mild cognitive impairment (MCI), differentiating them from AD patients and from normal elderly controls. This research project was planned to assess the accuracy of volumetric MRI to differentiate those groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
66
1
16

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(96 citation statements)
references
References 37 publications
13
66
1
16
Order By: Relevance
“…This finding agrees with previous studies reporting significant reductions of hippocampus volumes in AD compared to MCI patients [40] and with longitudinal studies [22] suggesting that hippocampus volume continues to shrink even in manifest stages of AD. One previous study reported reduced amygdala volumes in AD compared to MCI patients [5]. The effect size for amygdala volume reduction was -1.0 for left and -1.1 for right amygdala in this previous study which is within the expected range of effect size estimates as defined by the 95% confidence limits of the sampling distribution of the multicentre effect sizes from our study (figures 2 and 4).…”
Section: Discussionsupporting
confidence: 87%
“…This finding agrees with previous studies reporting significant reductions of hippocampus volumes in AD compared to MCI patients [40] and with longitudinal studies [22] suggesting that hippocampus volume continues to shrink even in manifest stages of AD. One previous study reported reduced amygdala volumes in AD compared to MCI patients [5]. The effect size for amygdala volume reduction was -1.0 for left and -1.1 for right amygdala in this previous study which is within the expected range of effect size estimates as defined by the 95% confidence limits of the sampling distribution of the multicentre effect sizes from our study (figures 2 and 4).…”
Section: Discussionsupporting
confidence: 87%
“…In blood testing for E4 allele, 20 control patients (healthy older individuals), 41 patients with Alzheimer's and 21 with mild cognitive impairment (MCI) were analyzed. In this study, Bottino et al (2002) discovered rates that indicate that older people with E4 allele have 2.4 times more risk of developing Alzheimer's disease.…”
Section: Dementiasmentioning
confidence: 97%
“…The presence of the two older groups (second and the third) in our study, in which age was not significantly different but the number of lipofuscin-bearing neurons and CA were, might be explained as the consequence of different brain aging patterns [49]. Finally, such a metabolic state of the parahippocampal gyrus neurons can indirectly support Keller's [4] hypothesis that such senescence-related changes, like CA and lipofuscin deposits, might represent predecessors for more serious changes, like the ones observed in the early phase of AD in the entorhinal area as part of the parahippocampal region [5][6][7][8][9][10][11][12][13][14][15]. Future research should include the development of in vivo methods of CA and lipofuscin deposit detection and quantification in the brain of the elderly individuals.…”
mentioning
confidence: 90%
“…Taking into the consideration the importance of the MTL in memory processing, a large number of cross-sectional volumetric neuroimaging studies were performed. They predominantly focused on the comparison of MTL structure volumes, or the degree of their atrophy, between healthy individuals, age-matched cases suffering from mild cognitive impairment (MCI) and cases at different stages of Alzheimer's disease (AD) [5][6][7][8][9][10][11][12][13][14][15]. Their results showed a significant reduction of MTL component volumes in cases with mild cognitive impairment and AD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation